2021
DOI: 10.1002/uog.22106
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COL4A1 and COL4A2 mutations in severe fetal multifocal hemorrhagic and/or ischemic cerebral lesions

Abstract: What are the novel findings of this work? This is the first prenatal series of cases establishing the prevalence of COL4A1 and COL4A2 gene mutations among fetuses presenting with a phenotype suggestive of cerebral injury, specifically severe and/or multifocal hemorrhagic or ischemic-hemorrhagic cerebral lesions. These anomalies could be of different ages and associated with schizencephaly or porencephaly. What are the clinical implications of this work?COL4A1 and COL4A2 gene mutations should be sought systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
0
24
0
2
Order By: Relevance
“…Although the condition is rare and the prevalence currently unknown, 1 one series found that, of pregnancies diagnosed with fetal intrauterine multifocal or severe hemorrhage or multifocal ischemic-hemorrhagic cerebral lesions, 5 of 18 harbored pathogenic COL4A1 mutation, suggesting that COL4A1 mutation is an important contributor to fetal brain maldevelopment. 6 Imaging studies 4 and animal modelling 3 have suggested that the congenital central nervous system abnormalities are the result of microvascular disease, often with the added physiological stress of parturition, but to date there are no reported pathological studies of human fetal histopathology. Moreover, despite the well-documented association of post encephaloclastic brain abnormalities and abnormal placental histopathology, 7 placental pathology has up to now been unreported for these cases.…”
Section: Introductionmentioning
confidence: 99%
“…Although the condition is rare and the prevalence currently unknown, 1 one series found that, of pregnancies diagnosed with fetal intrauterine multifocal or severe hemorrhage or multifocal ischemic-hemorrhagic cerebral lesions, 5 of 18 harbored pathogenic COL4A1 mutation, suggesting that COL4A1 mutation is an important contributor to fetal brain maldevelopment. 6 Imaging studies 4 and animal modelling 3 have suggested that the congenital central nervous system abnormalities are the result of microvascular disease, often with the added physiological stress of parturition, but to date there are no reported pathological studies of human fetal histopathology. Moreover, despite the well-documented association of post encephaloclastic brain abnormalities and abnormal placental histopathology, 7 placental pathology has up to now been unreported for these cases.…”
Section: Introductionmentioning
confidence: 99%
“…COL4A1 and COL4A2 ‐related disorders are a group of rare genetic multisystem conditions, also known as Gould syndrome, with associated clinical findings ranging from incidental porencephaly on MRI to significant neurological impairment, including developmental delay and movement and seizure disorders (Table S3) 1–3 . In two case series of porencephaly or adult‐onset cerebral hemorrhage, the prevalence of COL4A2 mutations was between 3.1% and 5.7% 3,4 . In a recent retrospective analysis of 18 fetuses presenting with severe, multifocal ischemic or hemorrhagic cerebral lesions, five had pathogenic COL4A1 mutations identified after delivery 5 .…”
Section: Figurementioning
confidence: 99%
“…Some children may present milder symptoms, such as isolated minor intellectual disability, or soft motor signs. In the most severe cases, the diagnosis can be made after a late miscarriage, or during pregnancy with ultrasound examination showing a large porencephalic cavity [ 27 ]. Fetal MRI may be particularly helpful to detail smaller brain lesions and to lead to the decision of medical abortion [27] .…”
Section: Haemorrhagic Angiopathy Due To Mutations In the Coding Regio...mentioning
confidence: 99%
“…The strong influence of birth trauma in triggering perinatal hemorrhages was demonstrated with the drastic reduction of perinatal hemorrhage in mutant mice delivered surgically [3] . In addition to the incomplete penetrance, the high rate of de novo mutations in COL4A1 and COL4A2 genes explain why numbers of affected children present as sporadic cases [27] .…”
Section: Haemorrhagic Angiopathy Due To Mutations In the Coding Regio...mentioning
confidence: 99%